Analisis Perhitungan Kapitasi pada Fasilitas Kesehatan Tingkat Pertama yang Bekerja Sama dengan BPJS Kesehatan KCU Kota Bogor Tahun 2015 - Kurnia, Ayu Novia; Nurwahyuni, Atik (UI Scholars Hub, 2017)
Based on PMK No. 69 in 2013, capitation is set at the same tariff for all age groups and only distinguished for each primary health care. Capitation is not adjusted by individual risk. This study aimed to calculate the capitation by age, using cross sectional design. The result of this study was capitation by age groups at the primary health care level. It was indicated that there was different capitation between age groups, with higher capitation observed in the age group of 0-4 and ≥50 years old and declining in productive age.